Frost resistance evaluation of the common millet (Panicum miliaceum L.) varieties - Kalinová, Jana (Agricultura (Maribor), 2005)
Trade liberalization for new member states (NMS) of the European Union (EU) following the recent EU accesion towards the East, tends to lead to an increase in trade flows among current EU-25 members. The trade creation effects induce the increased traded volume and the diversified trade types. These development patterns are revealed also in agricultural and food trade inNMS. Comparisons of the Slovenian agricultural and food trade with the similar trade for the other NMS are conducted with the emphasis on distinctionbetween primary and processed agricultural and food products. On the basis of the analysis it has been faund that the prevailing trade type is the inter-industry trade, which implies higher adjustment cost of displacementof resources across different industries. Intra-industry trade, which is often observed in trade among countries with similar factor endowments and smaller economic distances, represents only minor part of NMS-trade in agri-food products. Trade specialization, trade patterns, and trade geography in agri-food products imply some similarities with developing countries with less competitive agricultural and facto sector.
Keywords: poljedelstvo; proso; temperatura; rast